2016
DOI: 10.5326/jaaha-ms-6363
|View full text |Cite
|
Sign up to set email alerts
|

Use of Contrast-Enhanced Ultrasound in the Differential Diagnosis of Adrenal Tumors in Dogs

Abstract: We evaluated the diagnostic accuracy of the contrast-enhanced ultrasonography (CEUS), using a second-generation microbubble contrast agent, in differentiating the different types of adrenal mass lesions in 24 dogs. At B-mode ultrasound, 9 lesions involved the right adrenal gland, 14 the left, and 1 was bilateral. Each dog received a bolus of the contrast agent into the cephalic vein, immediately followed by a 5-mL saline flush. The first contrast enhancement of each adrenal lesion was evaluated qualitatively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 29 publications
1
29
2
2
Order By: Relevance
“…Contrast enhanced ultrasound utilizes gas‐filled microbubbles administered intravenously to obtain real‐time perfusion images of target organs and/or lesions . Recently, we used contrast‐enhanced ultrasound to diagnose gallbladder wall necrosis/rupture in dogs with a sensitivity and specificity of 100% .…”
Section: Introductionmentioning
confidence: 99%
“…Contrast enhanced ultrasound utilizes gas‐filled microbubbles administered intravenously to obtain real‐time perfusion images of target organs and/or lesions . Recently, we used contrast‐enhanced ultrasound to diagnose gallbladder wall necrosis/rupture in dogs with a sensitivity and specificity of 100% .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported the utility of CEUS in the diagnosis of lesions in the spleen and pancreas in dogs [20,29]. However, only a limited number of reports have described the usefulness of CEUS in the diagnosis of normal canine adrenal gland, pituitary-dependent hyperadrenocorticism, and adrenal tumors [2,[23][24][25]. In a previous study on CEUS for the diagnosis of adrenal tumors, the combination of enhancement degree and vascularity demonstrated to differentiate among CA, CAC and PHEO with an accuracy of 91.7% [2].…”
mentioning
confidence: 99%
“…However, only a limited number of reports have described the usefulness of CEUS in the diagnosis of normal canine adrenal gland, pituitary-dependent hyperadrenocorticism, and adrenal tumors [2,[23][24][25]. In a previous study on CEUS for the diagnosis of adrenal tumors, the combination of enhancement degree and vascularity demonstrated to differentiate among CA, CAC and PHEO with an accuracy of 91.7% [2]. We hypothesized that CEUS is a convenient and promising technique for the differential diagnosis of canine adrenal tumors.…”
mentioning
confidence: 99%
“…Nevertheless, there is only one preliminary study in veterinary medicine comparing the use of US and/or CT for the evaluation of adrenal tumors in dogs and the detection of tissue invasion or thrombus [25]. Two studies described CEUS pattern of adrenal tumors in dogs [26,27], but a detailed description of the thrombus enhancement was not provided.…”
Section: Discussionmentioning
confidence: 99%